EVALUATION OF ACTIVATED CHARCOAL SAMPLER TUBES - P. Nassiri; F. Golbabaie; K. Mehrain; A. Hematian (Tehran University of Medical Sciences, 1994)
This study has been conducted to evaluate the effectiveness of the local made charcoal tubes against adsorption of benzene, toluene and xylene vapors. Results indicate that desorption capacity and the recovery percentage decrease as the benzene, toluene and xylene concentrations and also relative humidity increase. It is concluded that the water vapor is the major interfere in the adsorption of mentioned vapors when the air is passed through the activated charcoal bed. The experiments show that the local made charcoal tubes are suitable for sampling in the predicted ranges existing in the work place.